Enhanced polyunsaturated fatty acid production using food wastes and biofuels byproducts by an evolved strain of Phaeodactylum tricornutum. (January 2020) - Wang, Xiang; Balamurugan, Srinivasan; Liu, Si-Fen; Zhang, Man-Man; Yang, Wei-Dong; Liu, Jie-Sheng; Li, Hong-Ye; Lin, Carol Sze Ki
Graphical abstract: Highlights: Kitchen wastewater was utilized as a nutrient source in microalgal cultivation. Food waste hydrolysate and crude glycerol promote algal biomass and PUFA accumulation. Butylated hydroxytoluene alleviates ROS generation and regulates NADPH in lipogenesis. The resultant ARA, DHA and EPA content were 50.4, 30.5 and 232.8 μg/mg, respectively. Abstract: This study investigates the prospective of utilizing kitchen wastewater and food wastes, biofuels industry byproducts as alternative water and carbon sources. Kitchen wastewater did not impede cellular growth rate of the evolved Phaeodactylum strain E70, which indicates its potential as an alternative to freshwater resources. Among the organic wastes assessed, food waste hydrolysate significantly increased cell growth. Supplement of crude glycerol in cultivation medium enhances the total fatty acid content. Mixed food waste hydrolysate and crude glycerol remarkably increased both the cell density and total fatty acid content. Also, the supplement of butylated hydroxytoluene alleviated the oxidative stress induced by impurities in organic wastes and concomitantly increased microalgal total fatty acids and polyunsaturated fatty acids content. The experimental results reported in this study show that a waste-based biorefinery could lead to utilization of organic waste resources for the efficient production of value-added products.